Measurement Method for Imbalance Factors in Direct-Conversion Quadrature Radar Systems - Byung-Kwon Park; Yamada, S.; Lubecke, V. (IEEE microwave and wireless components letters, 2007)
In quadrature direct-conversion Doppler radar systems, the I and Q receiver channels are subject to amplitude and phase imbalance factors caused by circuit and component imperfections. This nonideality results in an undesired linear transformation of the baseband output signals which degrades output accuracy and sensitivity. With known imbalance factors, compensation can be achieved through digital signal processing, but accuracy is affected by circuit modifications required to determine those factors. Presented here is a new measurement method for I/Q imbalance factors that can be performed without significant modification to the radar system, allowing more precise imbalance correction to be achieved. A phase shifter is introduced at the receiver input to simulate a target approaching with constant velocity, resulting in sinusoidal outputs which can be easily compared to determine phase and amplitude imbalance